Ударопрочные композиции на основе полидициклопентадиена - Лебедев, Владимир Владимирович (Технологический центр, 2012)
В статье получены полимерные композиции на основе полидициклопентадиена, которые синтезированы полимеризацией дициклопентадиена в присутствии синтетических каучуков. Данные композиции характеризуются повышенной ударной прочностью.

The article concerns the polymeric compositions on the basis of polydicyclopentadiene synthesized by polymerization of dicyclopentadiene in the presence of synthetic rubber. Polydicyclopentadiene is the new material, that can replace metal, glass-fiber plastic and polymer series because of its unique properties. Polydicyclopentadiene is characterized by low density, high impact resistance which remains at low temperatures (-69 C), high chemical and thermal stability in the wide range of operating temperatures and high resistance against corrosive mediums. The objective of the work is to obtain polydicyclopentadiene with high impact resistance by polymerization of dicyclopentadiene in the presence of synthetic ethylenepropylene rubber. It was shown that the insertion to polydicyclopentadiene of the testing rubber at 3% mass concentration increases the impact resistance up to acceptable index in comparison with the data for trade sample Telene.
Impact resistant compositions on the basis of polydicyclopentadiene
Keywords: ударная прочность; каучуки; переработка; синтезирование; полимеризация; polydicyclopentadiene; impact resistance; compositions; rubber